PENGARUH KEPEMIMPINAN, KOMPENSASI TIDAK LANGSUNG, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN - Dian Okta Meryana; Very Cyasmoro (LPPM Universitas Asa Indonesia, 2015)
Purpose- is to findout the effect of lewadership, compensation against employee’s performance Design/methology/approach- The permanent and contracted employees are selected as the respondent of this research. The whole staffs are taken as respondent by questionaire. Data analyzed by multiple regression. Findings- Leadership, compensation are the major factors in influencing the employee’s performance. Limitation of the research : This research is not assigned to include other variable that also significant in boosting performance by adding promotion, for instance. Practrical Implication: It is strongly recommended to have the good and proper combination of leadership and compensation to keep employees working well and welfare well to